Pen of iron American prose and the King James Bible - Alter, Robert (Princeton, N.J. : Princeton University Press, 2010)
In this book, biblical translator and literary critic Robert Alter traces some of the fascinating ways that American novelists--from Melville, Hemingway, and Faulkner to Bellow, Marilynne Robinson, and Cormac McCarthy--have drawn on the rich stylistic resources of the canonical English Bible to fashion their own strongly resonant styles and distinctive visions of reality. --from publisher description
America as a Scriptural culture -- Style in America and the King James version -- Moby-Dick : polyphony -- Absalom! Absalom! : lexicon -- Seize the day : American amalgam -- The world through parataxis.
Includes bibliographical references and index.
Description based on print version record.
Keywords: American literature -- History and criticism; Bible. -- Versions -- Authorized -- Influence; Bible and literature; Bible -- In literature; Electronic books; LITERARY CRITICISM / American / General